2012
DOI: 10.1007/s12192-012-0347-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 is inactivated by amino acid deprivation

Abstract: Mammalian cells respond to a lack of amino acids by activating a transcriptional program with the transcription factor ATF4 as one of the main actors. When cells are faced with cytoplasmic proteotoxic stress, a quite different transcriptional response is mounted, the heat shock response, which is mediated by HSF1. Here, we show that amino acid deprivation results in the inactivation of HSF1. In amino acid deprived cells, active HSF1 loses its DNA binding activity as demonstrated by EMSA and ChIP. A sharp decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
32
1
Order By: Relevance
“…AMPK can also regulate the HSR indirectly through its substrate PGC1α, a regulator of mitochondrial biogenesis that interacts with HSF1 during fasting in mouse livers and primary hepatocytes [17], thereby repressing the HSR when energy availability is low. Furthermore, HSF1 is inactivated by amino acid deprivation [32]. A potential mechanism involves mTORC1, a key regulator of translation that depends on amino acid levels, which promotes HSF1 activity through phosphorylation at Ser326 [33].…”
Section: Regulation Of Hsf1 By the Proliferative And Metabolic Statesmentioning
confidence: 99%
“…AMPK can also regulate the HSR indirectly through its substrate PGC1α, a regulator of mitochondrial biogenesis that interacts with HSF1 during fasting in mouse livers and primary hepatocytes [17], thereby repressing the HSR when energy availability is low. Furthermore, HSF1 is inactivated by amino acid deprivation [32]. A potential mechanism involves mTORC1, a key regulator of translation that depends on amino acid levels, which promotes HSF1 activity through phosphorylation at Ser326 [33].…”
Section: Regulation Of Hsf1 By the Proliferative And Metabolic Statesmentioning
confidence: 99%
“…The significant increase of plasma BHBA in response to LPD is the biochemical result of the physiological imbalance of the experimental cows and strengthens the power of O 2 P-HR method as a reliable measure of the energy status. (Hensen et al 2011). In a recent study, we showed that while Hsp70 attenuated in mammary gland epithelial cells, in response to caloric stress, FABP3 levels increased (Eitam et al 2009).…”
Section: Biochemical Indications For the Negative Energy Statusmentioning
confidence: 87%
“…In calorie-restricted cells, the age-related diminishment of HSF1 DNA binding is reversed [87]. Contrary to calorie restriction, amino acid deprivation impairs HSF1 DNA-binding activity and suppresses the expression of HSP mRNAs [88]. Similarly, depletion of glutathione also suppresses the HSF1 activation by heat shock [89].…”
Section: Metabolic Control Of the Psr In Diabetes Mellitusmentioning
confidence: 99%